PEMBENTUKAN SANGGAR TANI MUDA MELALUI PENGOLAHAN PISANG SABA Musa paradisiaca DI KALURAHAN SERUT - Mujtahidah, Tholibah; Pramesti Puspadewi; Dhita Pratama Putra; Amelia; Riswanda Himawa (JURNAL KASTARA, 2024)
Serut Village is one of the villages located in Gunungkidul, with the potential for extensive terraced agricultural land. One commodity that can thrive is the saba banana (Musa paradisiaca forma). Serut Village has a Farmers' Group (POKTAN) spread across 7 hamlets that are not yet integrated. The number of members aged 35 and over is still quite low because it is related to knowledge. This is due to the lack of interest of young people in the world of agriculture, which is considered unpromising, so the youth farmer studio program is a solution. This activity aims to cadre and train young people to become strong and independent millennial farmers, using several methods such as outreach, field schools, and training. The young farmers' studio in Serut Village focuses on developing agricultural technology and producing processed Saba bananas as a superior food product. To plan the implementation and sustainability process of the Ormawa HMPS Physics PPK program, we use methods such as field orientation, focus group discussions, training, mentoring, and evaluation with policymakers. The goal is to increase soft skills.